Effects of maternal parity on response of human myometrium to oxytocin and ergometrine in vitro. (November 2019) - Ryan, Gillian A.; Crankshaw, Denis J.; Morrison, John J.
Abstract: Objective: The aim of this study was to compare the effects of oxytocin and ergometrine on the intrinsic contractile parameters of human uterine smooth muscle at term between primiparous and multiparous women. Study design: Myometrial biopsies were obtained from women undergoing planned caesarean section at term. The biopsies were dissected into eight uniform strips and mounted in tissue baths for isometric recording. The strips were challenged with increasing concentrations of oxytocin and ergometrine. Parameters of contractile activity, including mean contractile force (MCF) and maximum amplitude of contractions (MAMP) were recorded and analysed. Results were compared between primiparous (Group 1) and multiparous (Group 2) women. Results: Myometrial biopsies were obtained from n = 11 donors (88 tissue strips), of which n = 5 were Group 1 and n = 6 were Group 2. In relation to oxytocin, the MAMP value observed was significantly greater in Group 2 than in Group 1 (151 ± 18mN vs 67 ± 14mN, P < 0.01). Regarding ergometrine, the MCF response was greater in Group 2 samples (24 ± 10 mN) than that in Group 1 (18 ± 2mN) (P < 0.05). Conclusion: Our findings highlight that women in a first pregnancy have a decreased response to both oxytocin and ergometrine in an in vitro setting when compared with women in a subsequent pregnancy, and this may have clinical implications regarding the management of postpartum haemorrhage in this cohort.